2021
DOI: 10.3389/fcell.2021.777007
|View full text |Cite
|
Sign up to set email alerts
|

Advances in RNA Epigenetic Modifications in Hepatocellular Carcinoma and Potential Targeted Intervention Strategies

Abstract: The current interventions for hepatocellular carcinoma (HCC) are not satisfactory, and more precise targets and promising strategies need to be explored. Recent research has demonstrated the non-negligible roles of RNA epigenetic modifications such as N6-methyladenosine (m6A) and 5-methylcytosine (m5C) in various cancers, including HCC. However, the specific targeting mechanisms are not well elucidated. In this review, we focus on the occurrence and detailed physiopathological roles of multiple RNA modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 130 publications
(128 reference statements)
0
5
0
Order By: Relevance
“…The current interventions for HCC are not satisfactory, and more precise prognostic indicator and promising strategies need to be explored. Recent studies point out that RNA modifiers play vital roles in HCC cell proliferation, exacerbation, and metastasis ( Zhu et al, 2021 ). However, these studies are mainly limited to several RNA modification regulators.…”
Section: Discussionmentioning
confidence: 99%
“…The current interventions for HCC are not satisfactory, and more precise prognostic indicator and promising strategies need to be explored. Recent studies point out that RNA modifiers play vital roles in HCC cell proliferation, exacerbation, and metastasis ( Zhu et al, 2021 ). However, these studies are mainly limited to several RNA modification regulators.…”
Section: Discussionmentioning
confidence: 99%
“…It plays an important role in cancerous cells' growth and proliferation, invasion, and malignant phenotype transformation. Promisingly, METTL1 is Frontiers in Genetics frontiersin.org a biomarker for the diagnosis and prognosis of HCC (Zhu L. R. et al, 2021). Despite being one of the most indispensable m 7 G-related genes, the overall relevance of METTL1 in cancer remains mostly unclear.…”
Section: Figurementioning
confidence: 99%
“…Epidemiological studies have indicated that liver diseases constitute an important part of global morbidity and mortality and have become a huge economic burden and an urgent public health crisis ( 2 , 3 ). However, due to the lack of understanding of their pathogenesis, late diagnosis and rapid progression, the clinical therapeutic strategies for liver diseases are still insufficient, which directly leads to unsatisfactory treatment effects ( 4 ). Therefore, the clinical treatment and management of liver diseases remains a considerable challenge, and there is an urgent need to deeply explore the mechanism and develop promising therapeutic drugs and strategies on this basis.…”
Section: Introductionmentioning
confidence: 99%